International human resources management : a new challenge - Trudel, Jean M. (2015)
One of the greatest challenges facing international organizations lies in their capacity to adapt their human resources management to the norms and values of different cultures. Organizations often confuse international human resources management and expatriate management. In doing so, they involuntarily block out scores of employees who are also active in the organizations. Country of origin, locations of recruitment and work, and geographical mobility constitute the fundamental elements of a complete managerial system. In essence, the communication and exchange capacities between the various groups some of which are more sedentary and others mobile are main considerations of international human resources as described by Huault (1998). This article proposes the review of four pillars to global human resources management for international organizations.